Factors Influencing the Buying Behavior of Gemstones and Yantras Among Households in West Bengal - Mazumder, Rabin (Indian Journal of Marketing, 2015)
The present research paper investigated the buying behavior of gemstones and yantras among households in West Bengal. Society has turned so competitive that every parent wants to give the best to their children so that they can fit in properly in this competitive world, and thereby achieve success. We are falling into distress due to numerous family-related problems. Pressures and tensions build up in every section of the society and it touches almost every person, whether it is a young or an aged person. Astrologers in India claim that they have a perfect solution to overcome all pressures and problems through gemstones and yantras. The study was based essentially on the primary data captured through a structured questionnaire and was administered to a total of 224 respondents. In order to find out the influencing factors behind the buying behavior of the respondents, factor analysis method was considered appropriate. The present study investigated the socioeconomic status of the households, when, and under whose influence they started using gemstones and yantras. The result of the analysis suggested that Parents' Influence, Trust in Deity, and Impact of Society were the three main factors that convinced the respondents into believing in such gemstones and yantras.